Actin-dependent membrane association of the APC tumour suppressor in polarized mammalian epithelial cells - Rosin-Arbesfeld, Rina (Oxford University Press, 2001)
Adenomatous polyposis coli (APC) is mutated in most colorectal cancers. APC downregulates nuclear β-catenin, which is thought to be critical for its tumour suppressor function. However, APC may have additional and separate functions at the cell periphery. Here, we examine polarized MDCK and WIF-B hepatoma cells and find that APC is associated with their lateral plasma membranes. This depends on the actin cytoskeleton but not on microtubules, and drug wash-out experiments suggest that APC is delivered continuously to the plasma membrane by a dynamic actin-dependent process. In polarized MDCK cells, APC also clusters at microtubule tips in their basal-most regions. Microtubule depolymerization causes APC to relocalize from these tips to the plasma membrane, indicating two distinct peripheral APC pools that are in equilibrium with each other in these cells. Truncations of APC such as those found in APC mutant cancer cells can neither associate with the plasma membrane nor with microtubule tips. The ability of APC to reach the cell periphery may thus contribute to its tumour suppressor function in the intestinal epithelium.